Ionospheric modeling and precision positioning global navigation satellite system (GNSS) - Nurul Fazirah, Ghazali; Sabira, Khatun; Kamarul Hawari, Ghazali; Fakir, Md Moslemuddin; Rashid, Mamunur; Bari, Bifta Sama (Springer Singapore, 2018)
In ionosphere, the total electron content (TEC) contributes a signifi-cant role in determining the scintillation. Ionospheric scintillation can affect se-verely in satellite-based navigation and communication systems. Thus, the study of TEC of ionosphere is very crucial. The correlation between TEN and temperature in different weather and time has been presented in this paper. The TEC data was taken from the global positioning system (GPS) receiver at Uni-versity Malaysia Pahang, Malaysia (120’24.7388’E and 36’14.5310’N ). TEC data was analyzed by the SPSS software and the results have shown that during dry weather, the